Strengthening rural development capabilities of local governments in Costa Rica and Honduras - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
This project is part of a hemispheric proposal which IICA, through PROADER, has formulated under the PLANLAC, and which is aimed at modernizing and strengthening the institutions of the public agricultural sector. The proposal aims to formulate and implement a project to strengthen the administrations of four municipalities in Costa Rica and Honduras that will serve as demonstration projects to carry out specific rural development actions using decentralized and participatory methods. In addition, the activities proposed contain actions that will make it possible to develop empirical decentralization-participation models for development that can be extrapolated to other municipalities with similar political and administrative features. The general objetive is to contribute to strengthening and updating the technical and administrative skills of the public agricultural sector at the national, regional and local levels, as pertains to the formulation and execution of rural development policies with a view to decentralizing the state and increasing the participation of civil groups.